Importance of technical-tactical and physical condition training in the training process of the Spanish Olympic judokas - Robles Rodriguez, A.; Robles Rodriguez, J.; Giménez Fuentes-Guerra, F. J.; Abad Robles, M. T. (Revista de Artes Marciales Asiaticas, 2018)
In order to know how the technical-tactical and physical condition training has been carried out during the process of sports training of Spanish Olympic judokas, a semi-structured interview was conducted to 20 judokas - 12 women (60%) and 8 men (40%). The results show that the Olympic judokas consider that tactical aspects have not been training adequately during their sports career, besides there is no unanimity regarding the age in which the technical aspects should be worked intensively. On the other hand, all of the interviewees give great importance to physical training. Most of them believe that this training should be done in an integrated way, completing it with specific physical training sessions. They consider strength as the most important physical capacity at early age categories, while endurance and strength were considered the most important at the elite level.